Association studies of ERCC1 polymorphisms with lung cancer susceptibility: a systematic review and meta-analysis. - Jinhong Zhu (Public Library of Science (PLoS), 2014)
Background Excision repair cross-complimentary group 1 (ERCC1) is an essential component of the nucleotide excision repair system that is responsible for repairing damaged DNA. Functional genetic variations in the ERCC1 gene may alter DNA repair capacity and modulate cancer risk. The putative roles of ERCC1 gene polymorphisms in lung cancer susceptibility have been widely investigated. However, the results remain controversial. Objectives An updated meta-analysis was conducted to explore whether lung cancer risk could be attributed to the following ERCC1 polymorphisms: rs11615 (T>C), rs3212986 (C>A), rs3212961 (A>C), rs3212948 (G>C), rs2298881 (C>A). Methods Several major databases (MEDLINE, EMBASE and Scopus) and the Chinese Biomedical database were searched for eligible studies. Crude odds ratios (ORs) with 95% confidence intervals (CIs) were used to measure the strength of associations. Results Sixteen studies with 10,106 cases and 13,238 controls were included in this meta-analysis. Pooled ORs from 11 eligible studies (8,215 cases vs. 11,402 controls) suggested a significant association of ERCC1 rs11615 with increased risk for lung cancer (homozygous: CC versus TT, OR = 1.24, 95% CI: 1.04-1.48, P = 0.02). However, such an association was disproportionately driven by a single study. Removal of that study led to null association. Moreover, initial analyses suggested that ERCC1 rs11615 exerts a more profound effect on the susceptibility of non-smokers to lung cancer than that of smokers. Moreover, no statistically significant association was found between remaining ERCC1 polymorphisms of interest and lung cancer risk, except for rs3212948 variation (heterozygous: CG vs.GG, OR = 0.78, 95% CI: 0.67-0.90, P = 0.001; dominant: CG/CC vs.GG, OR = 0.79, 95% CI: 0.69-0.91, P = 0.001). Conclusion Overall, this meta-analysis suggests that ERCC1 rs3212948 G>C, but not others, is a lung cancer risk-associated polymorphism. Carefully designed studies with large sample size involving different ethnicity, smoking status, and cancer types are needed to validate these findings.